Penerapan Website Interaktif dengan AI Agent sebagai Media Informasi dan Layanan Pemesanan Produk Durian Bhineka (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
Durian Bhineka Bawor is one of the leading local commodities of Alasmalang Village with high economic potential. However, product promotion and marketing activities are still dominated by conventional methods and limited local networks, resulting in restricted market access, low competitiveness, and the absence of structured product information documentation. This community service program aims to address these challenges through the implementation of an interactive website integrated with an AI Agent, serving as a centralized information platform as well as a digital product ordering service. The main objectives of this program are to strengthen local durian branding through the utilization of modern digital technology, expand market reach, and enhance community digital literacy. The implementation method was carried out in several stages, including program coordination and socialization, content needs assessment, website design and development, AI Agent and WhatsApp server integration, system testing, manager training, official deployment, and continuous assistance. The AI Agent provides interactive services in the form of product information delivery, personalized recommendations, and order facilitation directly connected to the admin dashboard and social media platforms, thereby accelerating transaction processes and improving consumer experience. The expected outcomes of this program include the establishment of a more professional, transparent, and efficient promotion and ordering system for Durian Bhineka Bawor products. The developed platform is expected to expand market access, increase product sales, and create new digital-based business opportunities. Furthermore, this program contributes to community empowerment by improving digital skills and technology management capabilities to support local economic independence and competitiveness.